Characterization of the complete chloroplast genome of Davidia involucrata Baill. (Nysssaceae), an endangered species endemic to China. Issue 1 (2nd January 2020) - Qi, Zhuo; Jiang, Zhenzhong; Jiao, Peng; Qu, Jing; Liu, Siyan; Yao, Dan; Wang, Piwu; Guan, Shuyan; Ma, Yiyong
Abstract: Davidia involucrata Baill. is a kind of tertiary paleotropical plant floristic relic species unique to China. This rare plant is disappearing due to poor adaptability and serious poaching. We first assembled the complete chloroplast (cp) genome of Davidia involucrata Baill. by Illumina paired-end reads data. The whole genome was 169, 085 bp, consisting of a pair of inverted repeats of 169, 379 bp, large single copy region and a small single copy region (96, 712 and 67, 667 bp in length, respectively). The cp genome contained 90 genes, including 64 protein-coding genes, 22 trRNA genes and 4 rRNA genes. The overall GC content of the whole genome was 38.04%. A neighbor-joining phylogenetic analysis demonstrated a close relationship between Davidia involucrata Baill. and Nyssa yunnanensis.